Association of aromatase levels with estrogen-related gene polymorphism CYP19 Rs10046 in breast cancer among Iraqi women - Hadi, Samah Fadhil; Ibraheem, Shrouk A. Hassan Al.; Abbas, Hamid Jaddoa (Edelweiss Applied Science and Technology, 2024)
Breast cancer (BC) is a significant health concern globally, and understanding its genetic basis can provide insights for better prevention and treatment strategies. The study offers significant insights into the diagnostic potential of biomarkers, the genetic risk factors associated with breast cancer, and underscoring the complex and multifactorial nature of the disease. Aromatase is a key enzyme in estrogen biosynthesis, and variations in the CYP19 gene may influence estrogen levels, impacting breast cancer development. Therefore, this study was investigated the association between the single nucleotide polymorphism (SNP rs10046) of aromatase CYP19 gene and aromatase level in breast cancer among Iraqi women and assessment of CA 15- 3 as standard tumor marker for breast cancer. A case-control study was conducted, including 70 Iraqi women diagnosed with Ductal Carcinoma and 67 age-matched healthy women as control group. Peripheral blood samples were collected from all participants. Genomic DNA was extracted using a standard protocol. The rs10046 single nucleotide polymorphism (SNP) in the CYP19 gene was genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. The PCR products were digested with specific restriction enzymes (Bsp1286 I (SduI)) and analyzed by gel electrophoresis. The results showed that E2, CA 15-3, and aromatase levels in patients have a highly significant differences (P value<0.05) when compared with the control group. Aromatase demonstrated high sensitivity, while CA 15-3 showed the greatest potential as a diagnostic marker. The CC genotype was more frequent in patients, this finding aligns with the hypothesis that genetic variations can influence breast cancer risk. In conclusion, the findings highlight the potential influence of the CYP19 rs10046 polymorphism on breast cancer risk among Iraqi women. CA 15-3 is a tumor biomarker of choice for the diagnosis and follow-up of breast cancer.